2010
DOI: 10.1186/1476-069x-9-36
|View full text |Cite
|
Sign up to set email alerts
|

Association between arsenic exposure and plasma cholinesterase activity: a population based study in Bangladesh

Abstract: BackgroundArsenic is a potent pollutant that has caused an environmental catastrophe in certain parts of the world including Bangladesh where millions of people are presently at risk due to drinking water contaminated by arsenic. Chronic arsenic exposure has been scientifically shown as a cause for liver damage, cancers, neurological disorders and several other ailments. The relationship between plasma cholinesterase (PChE) activity and arsenic exposure has not yet been clearly documented. However, decreased P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 36 publications
3
36
0
Order By: Relevance
“…Fourth, there are several other environmental pollutants (agricultural pesticide, for example) that may cause depression. Like As, organophosphate and carbamate pesticides decrease acetylcholinesterase in animals (Patlolla and Tchounwou, 2005) as well as in humans subjects (Ali et al, 2010). Despite these shortcomings, our sample size was large enough to conclude that there was convincing evidence to support the association between chronic low level As exposure and depression and neurobehavioral changes in rural women.…”
Section: Factorsmentioning
confidence: 88%
“…Fourth, there are several other environmental pollutants (agricultural pesticide, for example) that may cause depression. Like As, organophosphate and carbamate pesticides decrease acetylcholinesterase in animals (Patlolla and Tchounwou, 2005) as well as in humans subjects (Ali et al, 2010). Despite these shortcomings, our sample size was large enough to conclude that there was convincing evidence to support the association between chronic low level As exposure and depression and neurobehavioral changes in rural women.…”
Section: Factorsmentioning
confidence: 88%
“…As for PChE activity results, Rustemeijer et al [33] found an association between PChE activity and the rate of triacylglycerol synthesis. Decreased PChE activity has been found in patients suffering liver dysfunction [1]. PChE activity was positively associated as well with serum concentrations of cholesterol and triglycerides and with measures of overweight, obesity, and body fat distribution [10].…”
Section: Discussionmentioning
confidence: 99%
“…There is a positive correlation between the concentration of arsenic in drinking water and the (Ali et al, 2010); suggesting that the measurement of arsenic concentration in nails can be one of the important markers of chronic arsenic toxicity (Karagas et al, 1996;Caussy, 2005).…”
Section: Discussionmentioning
confidence: 99%